7-9x=76-30x

Simple and best practice solution for 7-9x=76-30x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-9x=76-30x equation:


Simplifying
7 + -9x = 76 + -30x

Solving
7 + -9x = 76 + -30x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '30x' to each side of the equation.
7 + -9x + 30x = 76 + -30x + 30x

Combine like terms: -9x + 30x = 21x
7 + 21x = 76 + -30x + 30x

Combine like terms: -30x + 30x = 0
7 + 21x = 76 + 0
7 + 21x = 76

Add '-7' to each side of the equation.
7 + -7 + 21x = 76 + -7

Combine like terms: 7 + -7 = 0
0 + 21x = 76 + -7
21x = 76 + -7

Combine like terms: 76 + -7 = 69
21x = 69

Divide each side by '21'.
x = 3.285714286

Simplifying
x = 3.285714286

See similar equations:

| 2n+10=16 | | 6y-2=7y-2y | | 2y^2-6y-11= | | 2psq+5p=8 | | X^3+10x^2+17x=28 | | x+2/x-3=x-1/x+9 | | 40-5x=4x+20 | | 9x/x-3=54/x+7 | | log(x^2-6x)-log(x)= | | 8xsq-4x=24 | | 1.95y=y+10+1 | | 3x+3=x+85 | | x^2-13x=-22 | | 80+30t-5t^2=0 | | 122-6x=39x+17 | | 8x-14=2x+14 | | s=2nr | | (2x+9)(6x-7)=0 | | (4x-7)= | | (x^2)-6(x)-1=0 | | 9w^6+42w^5+24w^4= | | 24x-36x^2=0 | | 8(6x-7)=96x | | -1/4(12x+4)+1/7(49x+21) | | 8-7x=119-28x | | 2x+3=x+85 | | -x^2+17x-23=5x+9 | | x^4-4x^2-2=0 | | 1.16y=y+1+0.5 | | 50-7x=20x+20 | | 5x+4=28x+12 | | 1.16y=y+1+0.3 |

Equations solver categories